2006
DOI: 10.1534/genetics.105.050195
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 of Saccharomyces cerevisiae Inhibits Transcriptional Silencing

Abstract: Eukaryotic genomes contain euchromatic regions, which are transcriptionally active, and heterochromatic regions, which are repressed. These domains are separated by ''barrier elements'': DNA sequences that protect euchromatic regions from encroachment by neighboring heterochromatin. To identify proteins that play a role in the function of barrier elements we have carried out a screen in S. cerevisiae. We recovered the gene HHO1, which encodes the yeast ortholog of histone H1, as a high-copy modifier of barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
4
22
4
Order By: Relevance
“…A general role for Hho1p in the formation of DNA loops and for DNA compaction during stationary phase was also reported (62,63). In contrast, Hho1p has also been demonstrated to prevent the establishment of silent chromatin, perhaps by modifying the barriers that separate transcriptionally active chromatin from heterochromatin (57,(63)(64)(65). Thus, both H1 and Hho1p have been implicated in long-range DNA looping and DNA compaction; however, the molecular mechanisms by which these proteins exert such functions are likely to differ.…”
Section: Figmentioning
confidence: 84%
“…A general role for Hho1p in the formation of DNA loops and for DNA compaction during stationary phase was also reported (62,63). In contrast, Hho1p has also been demonstrated to prevent the establishment of silent chromatin, perhaps by modifying the barriers that separate transcriptionally active chromatin from heterochromatin (57,(63)(64)(65). Thus, both H1 and Hho1p have been implicated in long-range DNA looping and DNA compaction; however, the molecular mechanisms by which these proteins exert such functions are likely to differ.…”
Section: Figmentioning
confidence: 84%
“…Reactions were stopped by boiling mixtures for 5 min in an equal volume of 2ϫ SDS-PAGE buffer. Reaction products were subsequently separated by 15% SDS-PAGE, transferred onto nitrocellulose paper, and immunoblotted with antibodies as indicated in the figures and/or figure legends at the following concentrations: HIS probe (1:4,000; Santa Cruz), anti-H3K9ac (1:4,000; Abcam), anti-H3K56ac (1:4,000; a gift from J. Recht), anti-H3K56ac (1: 2,500; Upstate), anti-H3K12ac (1:4,000; Active Motive), and antiHho1(1:2,000) (a gift from Pierre Defossez [50]). Protein concentrations were assessed as required using NanoDrop 2000c (Thermo Scientific) using the Protein A280 application.…”
Section: Methodsmentioning
confidence: 99%
“…Microarray analyses have revealed that expression of very few genes is altered in cells lacking HHO1 (Freidkin and Katcoff, 2001; Hellauer et al ., 2001). Moreover, defects in gene silencing at the silent mating‐type loci or telomeres, phenotypes often associated with mutations that alter chromatin function, have not been observed in cells lacking histone H1 (Escher and Schaffner, 1997; Patterton et al ., 1998; Veron et al ., 2006). Evidence supporting a role for S. cerevisiae histone H1 in chromatin function has been provided by two reports.…”
Section: Introductionmentioning
confidence: 99%